2020
DOI: 10.28991/cej-2020-03091491
|View full text |Cite
|
Sign up to set email alerts
|

Study of PAN Fiber and Iron ore Adsorbents for Arsenic Removal

Abstract: The main idea to conduct this study is the treatment of hazardous arsenite (As+3)  and arsenate (As+5)from water by two efficient adsorbetns i.e. polyacrylonitrile fiber (organic) and iron ore (inorganic). Polyacrylonitrile (PAN) fibers were chemically modified prior to loading iron using a solution of diethylenetriamine and aluminum chloride hexahydrate. The characterization of PAN fibers was performed through FTIR spectroscopy, which shows the binding of functional groups on PAN fibers surfaces. Atomic absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…These systems are commonly founded on physicochemical collaborations between metal particles and utilitarian gatherings present on the cell surface, which incorporates ionexchange, complexion, electrostatic fascination, and micro precipitation (Mack et al, 2008). Bhatti et al (2020) proposed the removal of arsenic (as As 3+ and As 5+ ) by using polyacrylonitrile (PAN) fibre and iron ore as adsorbent. This study revealed that that the modified PAN had better adsorption efficiency than the iron ore adsorbent for the treatment of both As 3+ and As 5+ upon adsorption study.…”
Section: Background Of the Studymentioning
confidence: 99%
“…These systems are commonly founded on physicochemical collaborations between metal particles and utilitarian gatherings present on the cell surface, which incorporates ionexchange, complexion, electrostatic fascination, and micro precipitation (Mack et al, 2008). Bhatti et al (2020) proposed the removal of arsenic (as As 3+ and As 5+ ) by using polyacrylonitrile (PAN) fibre and iron ore as adsorbent. This study revealed that that the modified PAN had better adsorption efficiency than the iron ore adsorbent for the treatment of both As 3+ and As 5+ upon adsorption study.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Markedly, the hydroxyl groups of RBC600-nZVI were ominously augmented as compared with the RBC600, which supported relatively more adsorption pockets for Cr(VI) adsorption [31]. There was a sharp peak at 2924 cm −1 which contributed to C-H stretching vibration (-CH 3 or -CH 2 group) [30,32].…”
Section: Ftirmentioning
confidence: 92%
“…An absorption peak obviously occurred at 3440 cm −1 , which ranged between 3200 and 3500 cm −1 , representing the intermolecular stretching of the hydrogen (H) bonding and thereby representing the peak of the hydroxyl group [30]. Markedly, the hydroxyl groups of RBC600-nZVI were ominously augmented as compared with the RBC600, which supported relatively more adsorption pockets for Cr(VI) adsorption [31]. There was a sharp peak at 2924 cm −1 which contributed to C-H stretching vibration (-CH3 or -CH2 group) [30,32].…”
Section: Ftirmentioning
confidence: 98%
“…The factors such as, restrict pH range, swift organic-load variations, and the effluent's physical-chemical characteristics check the degradation efficiency of the biological processes that have been widely used for dairy wastewater treatment [5,6]. Adsorption is a promising technique because of its ease of use, increased proficiency, low-cost requirements, and great reproducibility [7]. Furthermore, because the process is usually reversible, the adsorbents can be readily regenerated and reused [8].…”
Section: Introductionmentioning
confidence: 99%